STUDI KOMPARASI HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA LULUSAN MADRASAH IBTIDAIYAH DAN SEKOLAH DASAR DI SMP MUHAMMADIYAH 5 SURAKARTA TAHUN AJARAN 2024/2025 - Afianto, Rozin; Nurhidayati, Indah; Nissa, Izzun Khoirun (MAMBA'UL 'ULUM, 2025)
This study aims to compare the learning outcomes of Islamic Religious Education (PAI) between students graduating from Madrasah Ibtidaiyah (MI) and Elementary Schools (SD) at SMP Muhammadiyah 5 Surakarta in the 2024/2025 academic year. A quantitative comparative approach was used to analyze the differences in PAI learning outcomes between the two student groups. The sample consisted of 40 students, with 20 MI graduates and 20 SD graduates, selected through simple random sampling. The results showed that the PAI learning outcomes of MI graduates had an average of 77.15, with 15% of students in the good category, 85% in the sufficient category, and 0% in the poor category. Meanwhile, the PAI learning outcomes of SD graduates showed an average of 84.35, with 20% in the good category, 60% in the sufficient category, and 20% in the poor category. Analysis using the Mann-Whitney U test revealed a significant difference in learning outcomes between MI and SD graduates, with an Asym. Sig. (2-tailed) value of 0.000 < 0.05. These findings indicate that educational background influences students' understanding of PAI, and thus, a more adaptive educational approach is needed to address these differences.